1 - Les perspectives de développement de l'industrie sidérurgique en Afrique - JORLIN, Yves (Africa Development, 1981)
In this article, the author is trying to examine the prospects of the iron and steel industry in sub-saharan Africa. After pointing out the weakness and steel industry in sub-saharan Africa. After pointing out the weakness of this industry both of the levels of production and consumption he focuses on production, imports and the production prospects. He then analyses briefly the main obstacles to the evolution of this industry and makes a few suggestions for its improvement. For the writer, the consumption of iron and steel products is rather limited compared to other non African countries. In fact its production is so low that nearly 95% of these pro- ducts are imported from abroad. Hence, the interest of the author in considering the origins of these importations. This study shows that not only do imports originate from four main exporters, namely Japan, France, Great Britain and West Germany but each of these exporters seems to specialize in one product. Then the author lists the most important obstacles to a genuine development of this industry as follows; local markets for this industry are not large enough as a result of the low level of demand per capita because of the small size of populations; lack of control in investments in this field coupled with high cost of investments and operations; low funding capacity of this sector; the generally limited availability of resources in iron and steel in this part of the continent; the world economic crisis. He concludes by suggesting that solutions to this problem may be found in the application of the notion of collective autonomy to that branch because of the following factors: the importance of investments; the rather big size of the integrated units of iron and steel industry compared to the small size of local markets; the unequal distribution of raw materials. Two of the potential problems in trying to achieve this collective autonomy reside in the selection of the country where these units are to be set up and the share of costs involved. Yves JORLIN, CREA - 20, Rue Chahid Khalef Mustapha, Ben-Aknoun, Alger - Algerie